AD 3 The physiological role(s) of brain rhythms. Issue 10 (7th September 2012) - Fries, P
Abstract : Pascal Fries Study of medicine at the University of Saarland (1991–1993) and at the Johann Wolfgang von Goethe University in Frankfurt (1993–1998). Doctorate at the Max Planck Institute for Brain Research and at the Johann Wolfgang von Goethe University in Frankfurt (1993–1999). Postdoc in the Laboratory of Neuropsychology at the National Institute of Mental Health, Bethesda, MD, USA (1999–2001). Principal Investigator at Donders Institute for Brain, Cognition and Behaviour, Radboud University, Nijmegen, Netherlands (2001–2009). Professor of Systems Neuroscience, Radboud University Nijmegen, Netherlands (since 2008). Scientific Member of the Max Planck Society, Director of the Max Planck Institute for Neurobiology, Martinsried, and Director of the Ernst Strüngmann Institute (ESI) in Cooperation with Max Planck Society, Frankfurt (since 2009). Attention is most likely implemented by modulations in the effective connectivity among brain areas. We have proposed that effective connectivity depends on rhythmic synchronisation. We have therefore assessed neuronal activity with 252 electrodes distributed across one hemisphere between primary visual cortex and prefrontal cortex. We find that attention is subserved by strong and specific enhancements of interareal synchronisation. The inter-areal influence is often directed, typically bottom-up in the gamma-band and top-down in the β-band. These results suggest that inter-areal synchronisation subserves effective inter-areal interactions.